Treatment of aging leachate using biochar from tapioca skin: article / Fatin Afiqah Alias and Prof. Madya Dr. Kamariah Noor Ismail - Alias, Fatin Afiqah; Ismail, Kamariah Noor
Biochar is believed to have the ability in treating aging leachate through contaminants adsorption mechanism due to its favorable physical or chemical surface characteristics. Biochar derived from tapioca skin was heated to a temperature of 300oC and analyzed for BET surface area. Jar test apparatus was used to study the ability of biochar in TSS, turbidity, color, COD and heavy metals removal. Through this study, pH of solution, biochar dosage and retention time were varied. Based on the result obtained, the surface area of biochar was 2.0131 m2/g with pore volume of 0.005343 cm3/g. Moreover, it was found that high pH solution can cause significant reduction of TSS, turbidity, color, COD and heavy metals concentration. However, variation in biochar dosage and retention time did not bring great impact to the pollutants removal in leachate. Various modifications should be done on the biochar surface to activate it and improve its efficiency through various contaminants removal so that allowable discharge standard requirement for leachate is met.